2017
DOI: 10.1007/s10753-017-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Inhibits Inflammation Through PI3K/Akt/HIF Signaling After Focal Cerebral Ischemia in Rats

Abstract: Salidroside is being investigated for its therapeutic potential in stroke because it is neuroprotective over an extended therapeutic window of time. In the present study, we investigated the mechanisms underlying the anti-inflammatory effects of salidroside (50 mg/kg intraperitoneally) in rats, given 1 h after reperfusion of a middle cerebral artery that had been occluded for 2 h. After 24 h, we found that salidroside increased the neuronal nuclear protein NeuN and reduced the marker of microglia and macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…In addition, AKT activation induces the expression of high levels of HIF-1, an important regulator of angiogenesis that can upregulate the expression of VEGF and other angiogenic factors, thereby promoting angiogenesis. HIF-1 affects vascular endothelial cells through the following mechanisms of action: (1) promoting the migration and proliferation of endothelial cells; (2) increasing vascular permeability, plasma protein exosmosis, and cellulose scaffold formation to help vascular endothelial cells migrate and provide support for vascular growth; and (3) activating the proteolytic enzyme system, degrading the extracellular matrix and promoting angiogenesis [109][110][111][112].…”
Section: Role In Controlling Angiogenesismentioning
confidence: 99%
“…In addition, AKT activation induces the expression of high levels of HIF-1, an important regulator of angiogenesis that can upregulate the expression of VEGF and other angiogenic factors, thereby promoting angiogenesis. HIF-1 affects vascular endothelial cells through the following mechanisms of action: (1) promoting the migration and proliferation of endothelial cells; (2) increasing vascular permeability, plasma protein exosmosis, and cellulose scaffold formation to help vascular endothelial cells migrate and provide support for vascular growth; and (3) activating the proteolytic enzyme system, degrading the extracellular matrix and promoting angiogenesis [109][110][111][112].…”
Section: Role In Controlling Angiogenesismentioning
confidence: 99%
“…PI3K/Akt signaling pathway has been shown to positively affect the translational as well as transcriptional initiation of the HIF-1α gene [17]. Interestingly, a research conducted by Wei et al [19] demonstrated that salidroside inhibits inflammation through PI3K/Akt/HIF signaling after focal cerebral ischemia in rats, in which indicates that SAL might attenuates Adriamycin-induced FSGS via targeting PI3K/AKT pathway. In our study, when treated with Adriamycin, the PI3K/AKT pathway was activated, which is confirmed by the high levels of PI3K and pAKt.…”
Section: Discussionmentioning
confidence: 99%
“…All of these papers indicated the tight relationship between PI3K/AKT and HIF-1α. Interestingly, a research conducted by Wei et al [19] demonstrated that SAL inhibits inflammation through PI3K/ Akt/HIF signaling after focal cerebral ischemia in rats. Based on these findings, we believe SAL may attenuate Adriamycin-induced FSGS through inhibiting HIF-1αvia targeting PI3K/AKT pathway, which finally attenuated inflammatory response and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…DMOG also prevented microglial and glial activation (Iba‐1 and GFAP immunolabeling). Although we have not evaluated it, other researchers have shown that HIF‐1α and its targets (e.g., erythropoietin) can exert antiapoptotic and anti‐inflammatory effects through ERK‐1/2 signaling and activation of PKB pathway (5558). Further studies are needed to clarify the molecular mechanisms underlying the neuroprotective effect of DMOG.…”
Section: Discussionmentioning
confidence: 99%